2011
DOI: 10.1111/j.1475-097x.2011.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of ultrasonographic measurement of the architecture of the vastus lateralis and gastrocnemius medialis muscles in older adults

Abstract: The ability of these tests to determine a real change in VL and GM muscle architecture is good on a group level but problematic on an individual level as the relatively large 95% ratio LOAs in the current study may encompass the changes in architecture observed in other training studies. Therefore, the current findings suggest that B-mode ultrasonography can be used with confidence by researchers when investigating changes in muscle architecture in groups of older adults, but its use is limited in showing chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 25 publications
7
71
0
Order By: Relevance
“…These findings are consistent with those of previous studies that investigated the architecture of the medial gastrocnemius muscle in young children (ICC of 0Á94-0Á98 for thickness and 0Á85-0Á96 for medial gastrocnemius muscle pennation angle) (Legerlotz et al, 2010) and older adults (ICC of 0Á92-0Á99 for thickness and ICC of 0Á85-0Á94 for medial gastrocnemius muscle pennation angle) (Raj et al, 2012), and it supported our primary hypothesis that RUSI measurements of medial gastrocnemius muscle thickness and pennation angle are adequately reliable for research and clinical use in poststroke patients. These findings are consistent with those of previous studies that investigated the architecture of the medial gastrocnemius muscle in young children (ICC of 0Á94-0Á98 for thickness and 0Á85-0Á96 for medial gastrocnemius muscle pennation angle) (Legerlotz et al, 2010) and older adults (ICC of 0Á92-0Á99 for thickness and ICC of 0Á85-0Á94 for medial gastrocnemius muscle pennation angle) (Raj et al, 2012), and it supported our primary hypothesis that RUSI measurements of medial gastrocnemius muscle thickness and pennation angle are adequately reliable for research and clinical use in poststroke patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with those of previous studies that investigated the architecture of the medial gastrocnemius muscle in young children (ICC of 0Á94-0Á98 for thickness and 0Á85-0Á96 for medial gastrocnemius muscle pennation angle) (Legerlotz et al, 2010) and older adults (ICC of 0Á92-0Á99 for thickness and ICC of 0Á85-0Á94 for medial gastrocnemius muscle pennation angle) (Raj et al, 2012), and it supported our primary hypothesis that RUSI measurements of medial gastrocnemius muscle thickness and pennation angle are adequately reliable for research and clinical use in poststroke patients. These findings are consistent with those of previous studies that investigated the architecture of the medial gastrocnemius muscle in young children (ICC of 0Á94-0Á98 for thickness and 0Á85-0Á96 for medial gastrocnemius muscle pennation angle) (Legerlotz et al, 2010) and older adults (ICC of 0Á92-0Á99 for thickness and ICC of 0Á85-0Á94 for medial gastrocnemius muscle pennation angle) (Raj et al, 2012), and it supported our primary hypothesis that RUSI measurements of medial gastrocnemius muscle thickness and pennation angle are adequately reliable for research and clinical use in poststroke patients.…”
Section: Discussionsupporting
confidence: 92%
“…1). A modified ankle-foot orthosis was placed on the foot and lower leg to fix the ankle joint angle at 90°(neutral position) (Raj et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported estimates of reliability were good to high. [13][14][15][16][17][18][19][20][21] With the exception of a study reported by Thoirs and Englsh, 15 the reported intrarater correlation coefficients (ICC) among studies ranged between 0.90 and 0.99. Thoirs and Englsh 15 reported that high test-retest reliability was indicated in the lower extremity when subjects were measured in a standing position (ICC, 0.70-0.89; 95% confidence interval (CI), 0.79-0.94 for anterior thigh and 0.49-0.84 for posterior thigh, respectively).…”
Section: Validity and Reliability Of Mt Measurementsmentioning
confidence: 99%